1968
DOI: 10.1126/science.162.3861.1487
|View full text |Cite
|
Sign up to set email alerts
|

Photoregulation of an Enzymic Process by Means of a Light-Sensitive Ligand

Abstract: A specific inactivator of chymotrypsin, p-azophenyldiphenylcarbamyl chloride, exists as two geometric isomers, cis and trans, which are interconvertible by means of light. The cis-isomer is five times more reactive than the more stable trans-isomer, and is obtained by exposure of the latter to light of 320 nanometer wavelength. The trans-isomer can be regained by exposure of the cis-isomer to light of 420 nanometer wavelength. This interconversion can be made to occur in aqueous solution in the presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
53
0
1

Year Published

1969
1969
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 7 publications
0
53
0
1
Order By: Relevance
“…Its photochromic azoderivative (II), N-p-phenylazophenyl-N-phenylcarbamyl chloride, can exist in trans-and cis-configurations. The equilibrium between the two forms may be shifted by illuminating I1 with light of a certain wavelength (Kaufman et al, 1968):…”
Section: Principle Ementioning
confidence: 99%
See 1 more Smart Citation
“…Its photochromic azoderivative (II), N-p-phenylazophenyl-N-phenylcarbamyl chloride, can exist in trans-and cis-configurations. The equilibrium between the two forms may be shifted by illuminating I1 with light of a certain wavelength (Kaufman et al, 1968):…”
Section: Principle Ementioning
confidence: 99%
“…It turned out (Kaufman et al, 1968) that cis-I1 inactivates a-chymotrypsin five times as fast as trans-11. Approximately the same differences in the rates of inactivation under the action of stereoisomers I1 (and also two other related compounds) were reported for acetylcholinesterase (Bieth et al, 1969 and1973).…”
Section: Principle Ementioning
confidence: 99%
“…1 The photosensitive compound, N-p-phenylazophenyl-N-phenylcarbamyl chloride2 (PAPC), is a specific inactivator of chymotrypsin.3 PAPC is a photochromic (or phototropic) molecule4 which, under the influence of light, can undergo a reversible configurational change involving the N = N bond, to yield either a cis or a trans isomer. The change in structure is influenced by the wavelength of light as follows: 320 nm trans = cis 420 nm Although both isomers could inactivate chymotrypsin, the cis isomer was found to be about five times more active.…”
mentioning
confidence: 99%
“…These stereoisomeric acylenzymes are interconvertible by means of light. Erlanger et al [2] found that it is possible to regulate the rate of interaction of chymotrypsin with p-azophenyldiphenylcarbamyl chloride by using light of the appropriate wavelength (the cis-isomer is five times as reactive as the more stable trans-isomer). The two systems [1,2] can be considered as models for some of the light-sensitive metabolic processes present in living organisms (cf.…”
mentioning
confidence: 99%
“…The two systems [1,2] can be considered as models for some of the light-sensitive metabolic processes present in living organisms (cf. [2]). Furthermore, it should be pointed out that light-regulated cis-trans isomerism is a part of the mechanism of vision [1,3].…”
mentioning
confidence: 99%